High temperature corrosion performance of ceria doped Cr3C2-NiCr coated superalloys under actual medical waste atmosphere. (2020) - Ahuja, Lalit; Mudgal, Deepa
Abstract: Incineration technique is well known process which has been adopted to burn medical or municipal waste. Burning of medical waste generates contaminated environment which can be harmful for the components of incinerator. As the temperature is very high in incinerator, austentic steel and superalloys are generally used in construction of the components. However these alloys also suffered corrosion which can be delayed for some time by providing a coating protection on the surface of the alloys before installation. Hence, in this study, ceria incorporated Cr3 C2 -NiCr coating powder was deposited on Superni 600 and Superco 605 superalloys. For deposition, one of the thermal spray techniques know as detonation gun was used. The coated samples were drilled to hang using wire in the secondary chamber of incinerator operating at 1050 °C for 1000 h in a hospital. It was observed that coated Superco 605 suffered more corrosion as compared to coated Superni 600.